Rara! : vodou, power, and performance in Haiti and its diaspora - McAlister, Elizabeth A. (University of California Press, 2002)
Rara is a vibrant annual street festival in Haiti, when followers of the Afro-Creole religion called Vodou march loudly into public space to take an active role in politics. Working deftly with highly original ethnographic material, Elizabeth McAlister shows how Rara bands harness the power of Vodou spirits and the recently dead to broadcast coded points of view with historical, gendered, and transnational dimensions.